«Cuadrúpedo intensivo»: Poetry and humanities in César Vallejo - Granados, Pedro (2021)
César Vallejo's posthumous poem "Four Consciousnesses..." suggests four distinct and autonomous conceptions of the humanities, as books or Western canon, peoples or cultures, narratives or prosopopoeia, and post-humanism or post-anthropocentrism. In this article we will review each of these notions and demonstrate that together they allow the Vallejian poetic subject to reach in his poetry his/our eloquent "intensive quadruped"; that is to say, the "quadruped" resting fully on the totality of its extremities. Through this complex, oscillating and productive conjunction, we will know how to immunize ourselves, together with Vallejo, against any essentialist identity melancholy (nationalist, territorial, ethnic or even linguistic) and any globalized or homogenizing identity proposal.